Acquisition for Sleep - Pehr-Johan Norbäck; Charlotta Olofsson; Lars Persson (Center for Economic Studies and ifo Institute (CESifo), 2020)
Within the policy debate, there is a fear that large incumbent firms buy small firms' inventions to ensure that they are not used in the market. We show that such "acquisitions for sleep" can occur if and only if the quality of a process invention is small; otherwise, the entry profit will be higher than the entry-deterring value. We then show that the incentive for acquiring for the purpose of putting a patent to sleep decreases when the intellectual property law is stricter because the profit for the entrant then increases more than the entry-deterring value does.
Keywords: G24; L10; L20; M13; O30; 330; acquisitions; innovation; sleeping patents; IP law; ownership